2019
DOI: 10.3389/fpsyg.2019.01705
|View full text |Cite
|
Sign up to set email alerts
|

From Experience to Memory: On the Robustness of the Peak-and-End-Rule for Complex, Heterogeneous Experiences

Abstract: Memory forms the input for future behavior. Therefore, how individuals remember a certain experience may be just as important as the experience itself. The peak-and-end-rule (PE-rule) postulates that remembered experiences are best predicted by the peak emotional valence and the emotional valence at the end of an experience in the here and now. The PE-rule, however, has mostly been assessed in experimental paradigms that induce relatively simple, one-dimensional experiences (e.g., experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 45 publications
(118 reference statements)
3
31
2
Order By: Relevance
“…Average valence, which some previous studies have claimed is a better predictor than peak-end valence for retrospective assessment [22,23], does not be the mediation in our study. However, immediate satisfaction fully mediated the relationship between peak-end valence and retrospective satisfaction, which was unexpected.…”
Section: Immediate Satisfaction Mediates the Effect Of Peak-end Valence On Retrospective Satisfactioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Average valence, which some previous studies have claimed is a better predictor than peak-end valence for retrospective assessment [22,23], does not be the mediation in our study. However, immediate satisfaction fully mediated the relationship between peak-end valence and retrospective satisfaction, which was unexpected.…”
Section: Immediate Satisfaction Mediates the Effect Of Peak-end Valence On Retrospective Satisfactioncontrasting
confidence: 78%
“…• Positive peak valence: the highest value for the emotional valence during the experience, which can happen at one or several steps during the experience [21,22]. • Negative peak valence: the lowest value for the emotional valence during the experience, which can happen at one or several steps during the experience [21,22]. • End valence: the final value for the emotional valence at the end of the experience.…”
Section: Peak-end Rulementioning
confidence: 99%
See 1 more Smart Citation
“…Peak-end theory posits that the best predictor of overall evaluation is an average of the strongest emotional moment, and the last emotional moment, of that experience (Kahneman, Fredrickson, Schreiber, & Redelmeier, 1993). This theory is largely based on studies of brief, simple experiences of pain, and does not hold for longer, more complex experiences such as workaday life or tourism, where the average of emotions experienced is a better predictor (Kemp, Burt, & Furneaux, 2008;Miron-Shatz, 2009;Strijbosch et al, 2019). These findings suggest that the more positive episodes that exist during an experience, regardless of their order, the more positive the overall evaluation will be.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These observations are insufficient to support the peak-end rule because there is an inherently high correlation between a peak value and the overall average of sequential data 44 , thus hindering reliable conclusions www.nature.com/scientificreports/ about the peak-end rule. In fact, some studies have reported conflicting results that the average score is better than the peak score as a predictor of overall evaluations of experiences 45,46 . In any case, simply calculating the correlation between a single value extracted from an overall dataset and a retrospective value is insufficient to validate the peak-end rule.…”
Section: Discussionmentioning
confidence: 99%